ضوابط الاستفادة من المزايا الاستثمارية في القانون الجزائري ‏ - حسونة, عبد الغني (جامعة الوادي University of Eloued, 2019)
‏ ‏ ضبط المشرع الجزائري مسألة الاستفادة و التمتع بالمزايا الاستثمارية بنوعين من الضوابط ، النوع الأول ‏ذو طابع موضوعي يتعلق بطبيعة الاستثمارات التي يمكنها الاستفادة من المزايا المقررة حيث نظم مسألة ‏التمتع بهذه المزايا و الحوافز لصالح مجموعة من النشاطات فقط ارتأى فيها أنها الأنسب لتمتعها بهذه ‏المزايا ، من جهة أخرى فصل المشرع في طبيعة المزايا التي يمكن أن تستفيد منها النشاطات الاستثمارية ‏بحسب أهمية ومكان تواجد تلك الاستثمارات ، أما النوع الثاني من الضوابط فهو ذو طابع إجرائي حيث لم ‏يرتب المشرع على مجرد إقراره بالمزايا تمتع المشاريع الاستثمارية المطابقة للضوابط الموضوعية لتلك المزايا ‏، و لكن يتعين ضرورة التقيد و الانضباط بجملة من التدابير و الإجراءات ، التي يؤدي عدم احترام ‏أحدها إلى حرمان المستثمر من تمتعه بالمزايا المقررة قانونا أو تجريده منها .‏ ‏ ‎ The Algerian legislator has defined the issue of the benefit and enjoyment of ‎investment privileges by two types of standards. The first type is of an ‎objective nature depending on the nature of the investments that can benefit ‎from the prescribed privileges. Where he organized the issue of enjoyment of ‎these privileges and incentives. In favor of a range of activities he considered ‎the most appropriate for their enjoyment of these privileges. On the other ‎side, the legislator detailed the nature of the privileges that investment ‎activities can benefit from them , depending on the importance and location ‎of such investments. As for the second type of standards is of a procedural ‎nature, where the legislator didn’t arrange for just its acknowledging of ‎privileges that the investment projects corresponding to the objective ‎standards of these privileges enjoy with those privileges, but it must adhere ‎and committ to a set of measures and procedures, the lack of respect for one ‎of them leads to deprive the investor from his enjoyment of privileges which ‎are prescribed by the law or his denudation of them ‎
Keywords: المزايا الاستثمارية ; تسجيل الاستثمار ; التحفيز الجبائي